Charged-particle timing with 10 ps accuracy using TimeSPOT 3D trench-type silicon pixels - Borgato, F.; Brundu, D.; Cardini, A.; Cossu, G. M.; Dalla Betta, G. F.; Garau, M.; La Delfa, L.; Lai, A.; Lampis, A.; Loi, A.; Obertino, M. M.; Simi, G.; et al. (Frontiers in Physics, 2023)
For the next generation of vertex detectors, the accurate measurement of the charged particle timing at the pixel level is considered to be the ultimate solution in experiments operating at very high instantaneous luminosities. This work shows that the 55 \mum X 55 \mum wide 150 mum thick 3D trench-type pixels, developed by the TimeSPOT Collaboration, achieve a time resolution close to 10 ps with minimum ionizing particles while maintaining a detection efficiency close to 100% when operated at a tilt angle larger than 10^o from normal incidence. This record performance is obtained with software-based constant-fraction algorithms applied to signal waveforms. However, time resolutions as good as 25 ps can be achieved using a simple leading-edge discriminating technique, without any amplitude correction. Similar timing performances can also be achieved when the charged particles cross two nearby pixels if both signal amplitudes are measured. 3D trench-type pixels, as of today, are the fastest charged-particles pixel detectors available and represent a very promising solution for the future upgrade of tracking systems of many HEP experiments operating in extreme conditions.